Modification of polyethersulfone with partially reduced graphene oxide and its water purification application - Teboho R. Motlokoa; Winny K. Maboya; Charity Mbileni-Morema; Sekomeng J. Modise; Bamidele J. Okoli (Desalination and Water Treatment, 2025)
Nanofiltration is mostly used to treat surface water and wastewater to remove contaminants like heavy metals, small organics, calcium, magnesium and reduce the water hardness. Enhancing membrane properties such as surface characteristics and pore structure can lead to improved separation performance, greater wettability, and a longer lifespan. The study introduces a novel approach for enhancing magnesium ion rejection using a polyether sulphone (PES) membrane embedded with a nanocomposite of partially reduced graphene oxide (rGO). The effect of varying concentration of rGO nanocomposite ranging from 1 to 5 wt% in the fabricated membrane was evaluated in terms of pure water permeation, salt rejection, morphology, and hydrophilicity. EDX analysis of rGO confirmed its partial reduction, evidenced by a decrease in oxygen content from 34.8 % to 27.6 %. The composite membrane demonstrates that incorporating PES and partially rGO improved the wettability, water flux and effective solute rejection due to reduction of the hydrophilic groups. PES with 5 wt% of rGO nanocomposite obtained the highest PWP at 38 L/m2h, whereas the highest rejections of monovalent and divalent salts were obtained by PES with 1 wt% rGO with 77 %, 81 % and 87 % salt rejections for Mg2 + , Na+ and Ca2+, respectively and with the PWP of 30 L/m2h. The decline in salt rejections at higher rGO concentrations suggests that aggregation and increased viscosity inhibited free space formation, negatively affecting permeability. The study shows that partial reduction of GO and its utilization as an additive in the PES casting solution can enhance the salt rejection due to reduced hydrophilicity.